Networked power and resistance in agrarian conflicts: A case study from Malin Deman, Indonesia - Fattarawati, Febby (SIMULACRA: JURNAL SOSIOLOGI, 2025)
The agrarian conflict in Malin Deman District, Mukomuko Regency, Indonesia, highlights persistent inequalities in land tenure, pitting local farmers against plantation companies and state institutions to reclaim ancestral land. Using a qualitative single case study approach, this study examines the power dynamics and social network structures that shape the conflict. Data was collected through in-depth interviews with civil society organizations involved in land advocacy and secondary sources, including agrarian reports, legal documents, and investigative news articles. Findings show that dominant actors-plantation companies and the regional government-exercise power through coercion, economic incentives, and control over legal narratives. Social network analysis indicates that the regional government has the highest degree of centrality and betweenness centrality, positioning it as a mediator and gatekeeper between corporate-government alliances and farmer advocacy groups. However, smallholder farmers remain marginalized, with limited access to information and decision-making processes. This study highlights the need for inclusive land governance and network-based mediation strategies to strengthen community bargaining power. Increasing transparency, promoting equitable policymaking and ensuring participatory mechanisms are critical to resolving agrarian conflicts in an equitable and sustainable manner. By addressing structural inequalities and empowering marginalized communities, this research contributes to the broader discourse on land rights and conflict resolution strategies.